A brief research report of suicide rates in the Brazilian elderly over a 12-year period: the lack of association of the "Setembro Amarelo" campaign for suicide prevention - Corrêa Matias Pereira, Camila; Najafi Moghaddam Gilani, Vahid; Nazif-Munoz, José Ignacio (Frontiers in Psychiatry, 2024)
Objective: Aiming to disseminate information related to suicide prevention in Brazil, the "Setembro Amarelo" campaign has been conducted since 2015. The objective of this study is to assess the association between this campaign and elderly suicide rates over a 12-year period.Methods: Data were gathered from the Mortality Information System and the Notifiable Diseases Information System, established by public institutions in Brazil. An interrupted time-series framework was applied to assess the association between the "Setembro Amarelo" campaign and suicide mortality rates in the elderly population (60 et plus) in the southeastern region of Brazil.We consider three monthly outcomes: all suicides, suicides in males and suicide in females. We operationalize the campaign assuming three effects: short-term, declining and sustained. The period of analysis was from 2011-2022.The suicide-mortality rate over time has remained stable; the average rate in the pre-campaign period was 0.028 and increased slightly to 0.035. Regardless of the campaign's operationalization and the outcome used, results show no significant associations between the campaign and elderly suicide rates.The campaign was associated with non-significant decreased effects of 15% (P=0.532) in the short term, and 16% (P=0.446) assuming the campaign was sustained.There is a lack of association between the campaign and suicide rates, among the elderly in Brazil's southeastern region. As suicide is complex and multifactorial, more research is needed. The campaign, while raising awareness and reducing stigma, may not reduce suicides. To reduce the suicide rate in the elderly requires addressing social, economic and cultural factors, multisectoral interventions, and upholding basic human rights.